2015
DOI: 10.21608/jfds.2015.48537
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Technological Studies on Some Medicinal Plants

Abstract: This study indicate the importance of some wild medicinal plants such as milk thistle seed and chicory seed. Therefore , chemical characteristies such as crude protein, ether extract, crude fiber, amino acids, fatty acids, vitamin C and minerals contents were determined. Also ,the antioxidative properties such as phenolic compounds and flavonoid compounds and scavenging activity on DPPH free radicals were also determined. Moreover ,the possibility to use these seeds in biscuit production, where the utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In general, all formulas enriched with MTSP are acceptable for the sensorial attributions. These results agree with [29] reported that addition of MTSP to WF at extent 5, 10 and 15% of biscuits was acceptable for the sensory evaluation. Shahat, et al [13] showed that the realized specifications of balady bread not affected by addition MTSP at 9%.…”
Section: The Chemical Composition Of Bread Sticks (ց ∕ 100 ց On Dry Weight Basis)supporting
confidence: 92%
See 2 more Smart Citations
“…In general, all formulas enriched with MTSP are acceptable for the sensorial attributions. These results agree with [29] reported that addition of MTSP to WF at extent 5, 10 and 15% of biscuits was acceptable for the sensory evaluation. Shahat, et al [13] showed that the realized specifications of balady bread not affected by addition MTSP at 9%.…”
Section: The Chemical Composition Of Bread Sticks (ց ∕ 100 ց On Dry Weight Basis)supporting
confidence: 92%
“…The for crude protein, 23.12% for ether extract, 4.98 for ash and 30.33% for crude fibre [29]. WF 72% extraction comprised 11.38% crude protein, 0.82% fat, 0.45% ash and 86.79% total carbohydrates [30].…”
Section: Proximate Composition Of Mtsp and Wf 72% Extraction Composite (ց ∕ 100 ց On Dry Basis)mentioning
confidence: 99%
See 1 more Smart Citation